Symptoms of being human - Garvin, Jeff (Balzer + Bray an imprint of HarperCollinsPublishers, 2016)
Some days Riley Cavanaugh identifies as a boy, and others as a girl. But Riley isn't exactly out yet: between starting a new school and having a congressman father running for reelection in über-conservative Orange County, the pressure is building. On the advice of a therapist Riley starts an anonymous blog to vent pent-up feelings and tell the truth of what it's really like to be a gender fluid teenager. But when the blog goes viral, Riley must make a choice: walk away from what the blog has created-- or stand up, come out, and risk everything.